2004
DOI: 10.1093/treephys/24.6.707
|View full text |Cite
|
Sign up to set email alerts
|

Growth, allocation and tissue chemistry of Picea abies seedlings affected by nutrient supply during the second growing season

Abstract: One-year-old Norway spruce (Picea abies (L.) Karst.) seedlings were grown hydroponically in a growth chamber to investigate the effects of low and high nutrient availability (LN; 0.25 mM N and HN; 2.50 mM N) on growth, biomass allocation and chemical composition of needles, stem and roots during the second growing season. Climatic conditions in the growth chamber simulated the mean growing season from May to early October in Flakaliden, northern Sweden. In the latter half of the growing season, biomass allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
3
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 44 publications
6
26
3
4
Order By: Relevance
“…fertilization when compared to conditions without fertilization despite the same watering regimes. These results indicated that supply fertilization treatments could reduce the growth of roots as well as promote the growth of shoots, especially the growth of leaves, as also previously observed (George et al, 1997;Berger and Glatzel, 2001;Ewers et al, 2001;Trapeznikov et al, 2003;Coleman et al, 2004;Kaakinen et al, 2004). Moreover, nitrogen deficiency suppresses growth rate and leaf photosynthesis (Zhao et al, 2003), and N pulse increases photosynthetic rates and thus growth (Warren et al, 2004).…”
Section: Tablesupporting
confidence: 79%
“…fertilization when compared to conditions without fertilization despite the same watering regimes. These results indicated that supply fertilization treatments could reduce the growth of roots as well as promote the growth of shoots, especially the growth of leaves, as also previously observed (George et al, 1997;Berger and Glatzel, 2001;Ewers et al, 2001;Trapeznikov et al, 2003;Coleman et al, 2004;Kaakinen et al, 2004). Moreover, nitrogen deficiency suppresses growth rate and leaf photosynthesis (Zhao et al, 2003), and N pulse increases photosynthetic rates and thus growth (Warren et al, 2004).…”
Section: Tablesupporting
confidence: 79%
“…In more southern areas with higher temperatures, a longer photoperiod and more amount of light in autumn, root growth may continue a few weeks longer as was the case in the study of Wallertz et al (2016). The previous observations that the growth of roots in conifer seedlings can continue in hydroponic cultures in October (Iivonen et al 1999;Kaakinen et al 2004) or in favorable temperature conditions throughout the year (Mattson 1986) is not possible in newly planted seedlings under a natural declining photoperiod, light and temperature conditions combined with planting stress in late-autumn plantings.…”
Section: Discussionmentioning
confidence: 72%
“…In growing seedlings, however, allocation of photosynthates to roots probably increased during the study period. For example, Kaakinen et al [18] found a considerable increase in root biomass simultaneously with ceasing stem elongation after mid-July in 1-yr-old Norway spruce seedlings that had initiated stem elongation in early June. In addition, growing seedlings initially had more unsuberized root biomass than dormant seedlings, which may have contributed to the greater water uptake and further, also greater root egress.…”
Section: Discussionmentioning
confidence: 99%